The Role Of Guidance and Counseling Information Services Through Interprofessional Education - Mardiani Bebasari; Nurhizrah Gistituati; Mega Iswari Biran; Solfema; Hadiyanto (Bisma The Journal of Counseling, 2022)
This article was created to find out how to describe the role of guidance and counseling information services through interprofessional education. The aim of IPE is the practice of inter-professional collaboration, which involves various professions in learning about how to work together by providing the knowledge, skills and attitudes needed to collaborate effectively. This research method uses library research to examine through writings from books regarding cooperative learning models in interprofessional education. Information services are guidance and counseling services that enable students to receive and understand various information that can be used as material for consideration and decision-making for the benefit of students. Information services are services that provide information needed by individuals. Guidance and counseling services have very important functions and roles in schools, especially for students. By providing BK services the development of students will be more optimal. Counseling guidance services focus on developing personal and social aspects as well as solving problems individually. With these services it is hoped that students will be in prime condition, so that they can learn and develop themselves personally. According to WHO Interprofessional education or IPE is an educational process that involves two or more types of professions. Interprofessional education can occur when several students from various professions learn about other professions, learn together with one another to create effective collaborations.